An Innovative Herbal Hair Tonic Derived from Purslane (Portulaca oleracea) Extract - Rahman, Nur Afanin; Humaerah, Sadhilah (Cognitia : International Engineering Journal, 2025)
The rising demand for natural and eco-friendly personal care  products has driven innovation in plant-based formulations. Portulaca species, rich in bioactive compounds, are potential candidates for use in hair tonic products due to their hair growth-promoting  properties. This study aims to analyze the phytochemical content of two Portulaca species and evaluate the effects of extract concentration on hair tonic formulation quality; Methods or process: The research was conducted at the Research Laboratory of FTI-UMI and involved several steps: sample preparation, extraction using the Soxhlet method, qualitative phytochemical analysis, formulation of hair tonic, and testing of pH, viscosity, density, and organoleptic properties; Results: The phytochemical screening confirmed the presence of active compounds beneficial for hair care. Among the formulations, Portulaca oleracea L. extract in Formulation 1 demonstrated the most suitable characteristics, with a pH of 4.13, fulfilling the Indonesian National Standard (SNI) for cosmetic products. Similarly, Portulaca grandiflora H. extract in Formulation 1 exhibited acceptable quality with a pH of 4.25; Conclusion: The study highlights the innovative potential of Portulaca-based hair tonics as environmentally friendly alternatives in the cosmetic industry. These findings support the development of sustainable herbal products with scientifically proven efficacy.